(untitled) (Medico Legal Update, 2021)
In 2020, Indonesia will hold regional head elections simultaneously in 270 regions covering 9 provinces, 224 districts and 37 cities, voting on 9 December 2020. This study aims to analyse the potential for general elections in the midst of Covid-19 pandemic in Indonesia..Descriptive qualitative research method are used in which the data is obtained through interactive discussions, interviews and document searches. The results of our analysis conclude that there are 4 potential vulnerabilities in the 2020 elections, namely the availability of the budget, the readiness of election organizers, the number of alleged violations and the level of community participation. Recommendations for this study are the efforts to collaborate, coordinate and communicate well between the government and the election organizer and increase public participation.